1998
DOI: 10.1136/bjsm.32.3.220
|View full text |Cite
|
Sign up to set email alerts
|

Sport and active recreation injuries in Australia: evidence from emergency department presentations.

Abstract: Objective-Despite the rise in specialist clinical services for the management of sports and active recreation injury, many patients attend hospital emergency departments for treatment. The purpose of this study was to describe sports injury cases presented to selected hospital emergency departments around Australia for the period 1989-1993. Methods-Routinely collected emergency department injury presentation data from the Australian National Injury Surveillance Unit were examined. Data on 98 040 sports and act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
140
0
4

Year Published

2000
2000
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(154 citation statements)
references
References 11 publications
10
140
0
4
Order By: Relevance
“…59 In Australia the Australian style of football, basketball, soccer, cricket, netball and rugby caused most fall injuries in sports. 47 In a Danish study boys were most often injured in soccer, skateboard, handball, gymnastics and basketball, and girls in handball, horseback riding, gymnastics, basketball and roller-skating. 165 …”
Section: Fallsmentioning
confidence: 99%
“…59 In Australia the Australian style of football, basketball, soccer, cricket, netball and rugby caused most fall injuries in sports. 47 In a Danish study boys were most often injured in soccer, skateboard, handball, gymnastics and basketball, and girls in handball, horseback riding, gymnastics, basketball and roller-skating. 165 …”
Section: Fallsmentioning
confidence: 99%
“…Overall, soft tissue injuries (contusions and abrasions) were the next most common type(s) of injuries reported, accounting for 15-36% of cases [17,18,23,26,29,41,43], although Belechri et al [42] reported a range of 17.4-55% in five European countries. This group also reported the greatest percentage of fractures (17-36%), possibly due to the high number of hand/finger injuries reported.…”
Section: Injury Severitymentioning
confidence: 99%
“…This group also reported the greatest percentage of fractures (17-36%), possibly due to the high number of hand/finger injuries reported. Generally, the range for fractures was 2.6-17.7% [17-19, 23, 26-28] although three studies reported fractures making up 26-28% of the total number of injuries [12,29,43]. Inflammatory conditions were rarely reported but Hickey et al [27] found medial tibial stress syndrome to be responsible for 33.3% of all lower extremity injuries in a study of elite junior females, with patellar tendinopathy the most common knee problem (35.7%).…”
Section: Injury Severitymentioning
confidence: 99%
See 2 more Smart Citations